Advance accounting - Hoyle, Joe (United State of America : Richard D. Irwin, Inc., 1991)
This textbook presents the fourth edition of advanced accounting that i have created over the past 13 or so years. In each of theses editions, i have worked to produce an efficient educational instrument, one that is comprehensive and interactive but also interesting to college students. From the day I first conceived of Advance Accounting in 1980, I have sought to produce a book that that is actually engaging to read, similar to a magazine or newspaper. I want this textbook to convey to students the reasons why I find financial accounting to be a mentally stimulating, challenging, and even exciting. Learning can only be maximized if the textbook is able to capture the attention of students so that they will read and think seriously about each topic.
Include index
English text.
Keywords: accoounting